Epidemiology and assessments of delirium in nursing homes and rehabilitation facilities: a cross-country perspective - Ornago, Alice Margherita; Pinardi, Elena; Ferrara, Maria Cristina; Timmons, Suzanne; Okoye, Chukwuma; Finazzi, Alberto; Mazzola, Paolo; Nydahl, Peter; Haken, Rebecca von; Lindroth, Heidi; Liu, Keibun; Morandi, Alessandro; et al. (European geriatric medicine, 2025)
Purpose Delirium represents a significant healthcare challenge in long-term care settings. This study aims to investigate the epidemiology of delirium in long-term care facilities (LTCFs) across various countries, examining point prevalence and assessment methods. Methods This descriptive analysis included data from 94 surveys conducted in LTCFs on World Delirium Awareness Day (WDAD), March 15th, 2023. Group comparisons were made between rehabilitation facilities (RFs) and nursing homes (NHs). Results Of the participating units/wards, primarily from Europe and Australia, 65 were RFs and 29 were NHs. The overall reported delirium point prevalence was approximately 12%, with higher rates in RFs than in NHs. While most units/wards reported using a validated delirium detection tool, notable differences emerged in the frequency of assessments, the personnel conducting them, and delirium awareness interventions across settings. Conclusion Despite the well-documented impact of delirium on residents, the international variability in clinical practices within LTCFs highlights the current inadequacy in adopting effective and consistent strategies to address this condition.